Peran Al-Hidayah dalam Membangun Kepemimpinan Berbasis Akhlak Mulia - Bahasoan, Aminah; Asep Asep (Institut Nalanda, 2024)
Abstract: Pengajian Al-Hidayah faces challenges with low participation and active involvement of its members in activities that could develop leadership skills. Therefore, this community service program aims to enhance the leadership spirit of its members through spiritual development methods and Islamic studies. The program was conducted at Grand Avira Hotel Ambon, involving more than 50 members as participants. The program combines mentoring, coaching, and interactive discussions, while utilizing social media as a platform for communication and online discussions to improve participant engagement. The implementation method is divided into three stages: preparation, execution, and evaluation. During the execution stage, participants took part in lectures and leadership simulations, designed to sharpen their communication and decision-making skills. The evaluation results showed that participants' motivation and satisfaction levels exceeded 80%, with active participation rates of 75% in simulations, 78% in group discussions, and 80% in online meetings. This program successfully enhanced participants' understanding and skills in Islamic leadership. The primary recommendation is to continue monitoring and conducting ongoing evaluations to further develop the program and adapt it to other communities, with a focus on strengthening member engagement and ensuring sustainable leadership regeneration.